2020
DOI: 10.3390/polym13010117
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Leather Waste Fibers in Polymer Matrix Composites Based on Acrylonitrile-Butadiene Rubber

Abstract: In this study, we present the fabrication of nitrile butadiene rubber/waste leather fiber (NBR/WLF) composites with different weight percentages of WLF and NBR (0/100, 20/80, 30/70, 40/60, 50/50, 60/40 wt/wt). WLF was prepared by cutting the scrap leathers from the waste product of the Vietnamese leather industry. Subsequently, in order to make the short fibers, it was mixed by a hammer mill. The characteristics of WLF/NBR composites such as mechanical properties (tensile strength, tear strength, hardness), dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…8,9,11 Besides, the finished leather (FL) scraps are also discarded as waste from the production factory, leading to environmental problem. 2,14 Several studies have investigated the incorporation of leather solid wastes as filler into various polymeric materials, such as high density polyethylene, 3 polycaprolactam, 11 poly (vinyl chloride) (PVC), 5 poly (lactic acid) (PLA), 8 polyamide 12 (PA 12), 8 thermoplastic elastomer (TPE), 8 thermoplastic polyurethane (TPU), 4,8 poly (vinyl butyral) (r-PVB), 13 acrylonitrile-butadiene rubber (NBR), 15,16 and natural rubber (NR) 1,6,7,9,10,17 to produce composite materials. Babanas et al 5 incorporated different loadings of WBL scraps (20À60 parts by weight per hundred (phr) of resin) into plasticized PVC to produce leather-like material that could be used in footwear industry.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,11 Besides, the finished leather (FL) scraps are also discarded as waste from the production factory, leading to environmental problem. 2,14 Several studies have investigated the incorporation of leather solid wastes as filler into various polymeric materials, such as high density polyethylene, 3 polycaprolactam, 11 poly (vinyl chloride) (PVC), 5 poly (lactic acid) (PLA), 8 polyamide 12 (PA 12), 8 thermoplastic elastomer (TPE), 8 thermoplastic polyurethane (TPU), 4,8 poly (vinyl butyral) (r-PVB), 13 acrylonitrile-butadiene rubber (NBR), 15,16 and natural rubber (NR) 1,6,7,9,10,17 to produce composite materials. Babanas et al 5 incorporated different loadings of WBL scraps (20À60 parts by weight per hundred (phr) of resin) into plasticized PVC to produce leather-like material that could be used in footwear industry.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, the threads were soaked in a toluene/polytetrafluoroethylene particle solution. The toluene solvent broke and roughened the rubber/polyester thread (as in a spider knot structure); however, the synthetic rubber core was not damaged owing to its high resistance to organic solvents and chemicals . Silica nanoparticles and tetrafluoroethylene microparticles penetrated and adhered to the pores (hollow parts) of the polyester (shell) fiber bundle and the rubber core, increasing the thread surface hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…The toluene solvent broke and roughened the rubber/polyester thread (as in a spider knot structure); however, the synthetic rubber core was not damaged owing to its high resistance to organic solvents and chemicals. 38 Silica nanoparticles and tetrafluoroethylene microparticles penetrated and adhered to the pores (hollow parts) of the polyester (shell) fiber bundle and the rubber core, increasing the thread surface hydrophobicity. The resulting changes in the wettability and structure of the thread surface improved the capacity of large-droplet growth and the water collection rate of rubber/polyester-m@ETT (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the treatment improved the tensile properties, hardness, rigidity, and abrasive resistance of the composites. Hang et al 25 proposed the manufacture of nitrile butadiene rubber and residual leather fiber composites with different weight ratios of leather. Their results showed that the tensile strength and tear resistance of composites increased with higher leather contents, demonstrating a great potential of these composites for manufacturing products such as floor coverings and playgrounds.…”
Section: Introductionmentioning
confidence: 99%